The Trends of Complicated Acute Colonic Diverticulitis—A Systematic Review of the National Administrative Databases - Roberto Cirocchi; Georgi Popivanov; Alessia Corsi; Antonio Amato; Riccardo Nascimbeni; Rosario Cuomo; Bruno Annibale; Marina Konaktchieva; Gian Andrea Binda (Medicina, 2019)
Background and Objectives: The diverticular disease includes a broad spectrum of different “clinical situations” from diverticulosis to acute diverticulitis (AD), with a full spectrum of severity ranging from self-limiting infection to abscess or fistula formation to free perforation. The present work aimed to assess the burden of complicated diverticulitis through a comparative analysis of the hospitalizations based on the national administrative databases. Materials and Methods: A review of the international and national administrative databases concerning admissions for complicated AD was performed. Results: Ten studies met the inclusion criteria and were included in the analysis. No definition of acute complicated diverticulitis was reported in any study. Complicated AD accounted for approximately 42% and 79% of the hospitalizations. The reported rates of abscess varied between 1% and 10% from all admissions for AD and 5−29% of the cases with complicated AD. An increasing temporal trend was found in one study−from 6% to 10%. The rates of diffuse peritonitis ranged from 1.6% to 10.2% of all hospitalizations and 11% and 47% of the complicated cases and were stable in the time. Conclusions: The available data precluded definitive conclusions because of the significant discrepancy between the included studies. The leading cause was the presence of heterogeneity due to coding inaccuracies in all databases, absence of ICD codes to distinguish the different type of complications, and the lack of coding data about some general conditions such as sepsis, shock, malnutrition, steroid therapy, diabetes, pulmonary, and heart failure.